2010
DOI: 10.1016/j.jacc.2010.02.076
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide in Pregnant Women With Heart Disease

Abstract: Many pregnant women with heart disease have increased BNP levels during pregnancy. Incorporating serial BNP levels in into clinical practice can be helpful, specifically in adjudicating suspected adverse cardiac events during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 27 publications
5
96
1
2
Order By: Relevance
“…Although NT-proBNP level, a more stable biomarker in the blood than BNP, has also been shown to be elevated in women with preeclampsia [20 -22], to our knowledge there have been no previous studies regarding either NT-proBNP or BNP levels in otherwise healthy women with twin pregnancies. The results of the present study suggested that twin pregnancy should be added to the list of conditions in which increased NT-proBNP levels are anticipated that includes cardiopulmonary diseases [7,12,13], infection [23,24], and hypertensive disorders [20 -22] during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although NT-proBNP level, a more stable biomarker in the blood than BNP, has also been shown to be elevated in women with preeclampsia [20 -22], to our knowledge there have been no previous studies regarding either NT-proBNP or BNP levels in otherwise healthy women with twin pregnancies. The results of the present study suggested that twin pregnancy should be added to the list of conditions in which increased NT-proBNP levels are anticipated that includes cardiopulmonary diseases [7,12,13], infection [23,24], and hypertensive disorders [20 -22] during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Serum BNP levels increase in response to volume or pressure overload in the non-pregnant state [8 -10] as well as the normal pregnant state resulting in approximately twofold higher levels than in non-pregnant women [11], and pregnancies complicated with cardiac and/or pulmonary diseases [12,13] and preeclampsia [13 -19]. These studies regarding BNP levels during normal singleton pregnancies indicated that BNP levels, once elevated to approximately twofold those in non-pregnant state, do not change during pregnancy until term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Tanous et al demonstrated that a small group of 66 pregnant women with congenital and acquired heart disease revealed a median BNP level over twofold than that found in the control group of 12 healthy pregnant women. 48 Although this work is based on few patients and does not consider only patients affected by CHD, it permits to hypothesize that BNP strongly correlates with adverse cardiac events in CHD patients. Actually, in this work all the women who manifested an adverse cardiac outcome (defined as arrhythmia requiring treatment, stroke, cardiac arrest or cardiac death, pulmonary edema, decline of NHYA functional class by at least two classes, or need for urgent invasive cardiac procedures during pregnancy or within six months after delivery) had an elevated BNP (>100 pg/mL).…”
Section: Risk Factorsmentioning
confidence: 99%
“…(10) For more details on the specific prediction rules, we would like to refer to the original articles. (7,(9)(10)(11)(12) …”
Section: Risk Stratifi Cationmentioning
confidence: 99%